Prevalence of depression among school going adolescents in an urban area of Karnataka, India: a cross sectional study - Sinha, Sweta; Patil, Manjula S.; Viveki, R. G.; Halki, Sunanda (International Journal Of Community Medicine And Public Health, 2020)
Background: World Health Organization (WHO) recognizes depressive disorders as priority mental health disorder of adolescence due to its high prevalence, recurrence, ability to cause significant complications and impairment. Emotional instability resulted in adolescent period make them vulnerable to depression. Depression is one of the under recognized health problem among adolescents. The aim of the study was to explore the prevalence of depression among school going adolescents. Methods: A cross sectional study was conducted among the school going adolescents of urban area of Belgaum, Karnataka. The self-administered questionnaire of Beck’s Depression Inventory (BDI) II was used to assess the prevalence of depression. Data was analysed using MS-Excel 2007, SPSS software version 22.0, proportion and chi-square test were applied. Results: The overall prevalence of depression in this study was 62.60%. Association between sex, type of family and socio-economic status was not statistically significant. Mild depression was more prevalent among the adolescents in the present study. Conclusions: We recommend that teachers and parents be made aware of this problem with help of school counsellors so that the depressed adolescent can be identified and helped rather than suffer silently.